‘Collected’ Pages for the Issipile (Teatro San Carlo, 1763)* - Maione Paologiovanni (Musicology Today, 2021)
During the 1763–64 season, numerous intersections and connections occur behind the scenes of the principal Neapolitan opera house of Teatro di San Carlo. On the one hand, the focus on Metastasian repertoire persists without interruptions – a long and boundless tradition which will only fade towards the end of the century; on the other hand, Hasse’s world still exerts its fascination.